Пошаговое объяснение:
[tex] \frac{(x - 5)}{3} = 8 \\ x - 5 = 24 \\x = 24 + 5 \\ x = 29 \\ \\ \frac{(6x + 7)}{7} = \frac{(5x - 3)}{8} \\ 8(6x + 7) = 7(5x - 3) \\ 48x + 56 = 35x - 21 \\ 48x - 35x = - 21 - 56 \\ 13x = - 77 \\ x = - \frac{77}{13} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
[tex] \frac{(x - 5)}{3} = 8 \\ x - 5 = 24 \\x = 24 + 5 \\ x = 29 \\ \\ \frac{(6x + 7)}{7} = \frac{(5x - 3)}{8} \\ 8(6x + 7) = 7(5x - 3) \\ 48x + 56 = 35x - 21 \\ 48x - 35x = - 21 - 56 \\ 13x = - 77 \\ x = - \frac{77}{13} [/tex]